Realization of Hybrid-Electric Powertrain System for a Three Wheeler Auto Taxi - Mohammad Saad Alam; Rakan C Chabaan (Institute of Advanced Engineering and Science, 2012)
In this paper, the mechanical powertrain of a conventional three wheeler auto taxi was first analyzed and converted into a hybrid electric power train for similar vehicle requirements. Packaging design strategy of key power train components have been calculated and proposed. The preliminary design is simulated as a series hybrid fuel cell Ni-MH battery vehicle model in PSAT software for a typical city driving cycle. Further an environmental and economic study has been prepared for the proposed vehicle by calculating the emission levels and payback period. This design can be implemented in the longer run on wide range of vehicles; thus creating independence from fossil fuels.